The effect of planting pattern and fertilizer rates on the accumulation of biological dry mass of rice - Muminova Mukhabat Gofurzhanovna; Kalandarov Bakhtiyor Iskandarovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract. This study investigated the effect of different planting schemes and mineral fertilizer (NPK) rates on the accumulation of dry matter and total biomass of rice plants under the soil-climatic conditions of the Tashkent region. The rice varieties Billur and Gulistan were used as research objects. The experiment included three fertilizer treatments (N60P60K90, N90P60K90, and N120P60K90) combined with different seedling densities (planting schemes). The results showed that increasing the nitrogen rate significantly enhanced both the dry mass of a single plant and the total dry biomass per unit area. The highest individual plant dry mass values were recorded under the 25×25 cm planting scheme combined with the N120P60K90 fertilizer rate. Wider spacing provided better access to light, nutrients, and moisture, which promoted greater biomass accumulation per plant. During the ripening phase, the total dry biomass of the Billur variety reached 24.4–29.6 t/ha depending on the treatment. It was observed that when plant density per unit area was low (wider spacing), the dry mass of an individual plant was higher. Conversely, when seedling density was high (narrower spacing), total biomass accumulation per hectare increased due to the greater number of plants, despite the lower dry mass per individual plant. Overall, the findings indicate that both planting pattern and nitrogen fertilizer rate play a decisive role in dry matter accumulation and biomass formation in rice. Optimizing the balance between plant density and mineral nutrition is essential for achieving maximum biological productivity under the given agro-ecological conditions.